HILIC UHPLC–MS/MS for fast and sensitive bioanalysis: accounting for matrix effects in method development. (October 2013) - Havlíková, Lucie; Vlčková, Hana; Solich, Petr; Nováková, Lucie
Background: Matrix effects are considered to be a main obstacle of quantitative bioanalytical LC–MS/MS methods. Therefore it is often required to minimize them in order to increase method reliability. HILIC has been referenced as one of possible approaches. However, there is a lack of experimental evidence in scientific literature so far.Methodology: Matrix effects were evaluated using spiked serum samples after SPE and protein precipitation prior to UHPLC–ESI-MS/MS. Chromatography was performed in both HILIC and reversed-phase mode. The influence of the matrix effects on the signal response was assessed using a set of 34 compounds of pharmaceutical interest and post-extraction addition approach.Results: The advantages and drawbacks of the HILIC and reversed-phase chromatographic modes were compared and discussed in detail.Conclusion: HILIC demonstrated the potential to reduce the occurrence of matrix effects when a more thorough sample pretreatment procedure such as SPE was applied.